Pengaruh Kecerdasan Emosional dan Efikasi Diri terhadap Pengambilan Keputusan Karier Generasi Z di Kabupaten Tasikmalaya - Najwa Nabila; Sri Sudiarti (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study focuses on Generation Z in Tasikmalaya Regency and investigates how self-efficacy and emotional intelligence influence career decision-making processes. The research was motivated by increasing youth unemployment and the growing number of NEET individuals, namely those not in education, employment, or training, which indicates a lack of readiness among young people in planning their professional future. This study employed a quantitative survey design, with data collected from 100 Generation Z respondents selected through purposive sampling. The data were analyzed using multiple linear regression with SPSS 31. The results show that emotional intelligence has a positive and significant effect on career decision-making, with a t value of 5.291 and a significance value of 0.000. Self-efficacy also has a positive and significant effect, with a t value of 4.153 and a significance value of 0.000. Simultaneously, emotional intelligence and self-efficacy significantly predict career decision-making, with an F value of 131.890 and a significance value below 0.001. The two variables explain 73.1 percent of the variance in career decision-making, while the remaining 26.9 percent is influenced by other variables not included in this study. These findings highlight the importance of strengthening self-efficacy and emotional intelligence to help Generation Z make more mature and well-directed career decisions.